TEMPAT PENYIMPANAN PERLENGKAPAN PEMBUATAN PIN - Darius Shyafary; Merlinda Wahyuni (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2018)
abstractIn this modern era, most people need objects that are useful for their daily routine and as a means of communication that usually form of identification or souvenir. One of the most common identification and souvenirs used by the public is the pins and key chains. Pick-knitting materials and key chains that belong to many diverse sizes should have a special storage area that can be used in addition to storing pin fixtures, but also used to protect from damage and not scattered anywhere. However, from the observation of some printing media in Samarinda one of them in Mabes O2, it is known that the storage of pin equipment that they use today is only a plastic paper stacked in a cardboard box or plastic so that the equipment makes the pin making material becomes very easy to mix. In a report entitled "Storage Place of Pin Making Equipment" has provided a new alternative in the development of pin storage equipment design. The purpose of this project is to design an innovate product that facilitates and accelerates the user in the production process of finishing pin or key chain. By using the methods that have been done are: field data collection, analysis, alternative design, development of selected design alternatives and final design, so that the design produced the storage equipment pin that has the concept of modern minimalist design style.Keywords: ID Card, Pin, Storage, Minimalist, Modern